Needlestick and sharp injuries among healthcare workers in hospitals: a mini-systematic review - Khraisat, Firas Shehadeh; Juni, Muhamad Hanafiah; Abdul Rahman, Anita; Md Said, Salmiah (American Association for Science and Technology, 2014)
Background: Needlestick and sharp injuries (NSSIs) are defined as percutaneous injuries with needles or sharp objects contaminated with blood or other body fluids. NSSIs are considered as a major occupational hazard among healthcare workers (HCWs) since needles and sharp objects are commonly used in hospitals. Objectives: The objective of this study is to conduct a systematic review on the published scientific literature to provide accurate assessment of needlestick and sharp injuries among healthcare workers including prevalence, risk factors, predictors, reporting, and interventions. Methods: The following selection criteria were used to perform a systematic search of the literature: research studies published in English language between 2011 and 2014, targeted population is the healthcare workers providing direct care to the patients in the hospitals. The outcome of the study is the needlestick and sharp injuries. The following databases were searched: ScienceDirect, Scopus, and EBSCO. The included search terms were: needlestick injury, sharp injury, NSI or NSSI and healthworkers. The search was limited to cross-sectional studies, retrospective studies, and randomized controlled trials conducted in the hospital. The criteria to select articles were limited to peer-reviewed scientific publications and review articles were excluded. Result: Based on the inclusion and exclusion criteria, screening was done to the 35 articles. 18 articles were found eligible to be included while 17 studies were excluded. The included studies consisted of 10 cross-sectional, 7 retrospective, and 1 intervention study. In general, higher NSSI rates were found in nurses (average reported between 64.1% - 44.3%) compared to other occupational groups (average NSSI rate reported were first year resident physician 45%, interns 26% and housekeeper 12.3%). Conclusion: NSSIs is an important occupational hazard among health workers in their daily working. More emphasis must be put on investigating methods and strategies to reduce NSSIs. Safety devices must be used more by HCWs to reduce NSSIs along with planning educational and training programs with close monitoring to practices.